1990
DOI: 10.1021/jm00172a032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and pharmacological evaluation of a series of new 1,4-disubstituted 3-methyl-piperidine analgesics

Abstract: The synthesis and intravenous analgesic activity of a series of 3-methyl-4-(N-phenyl amido)piperidines, entries 34-79, is described. The methoxyacetamide pharmacophore produced a series of compounds with optimal analgesic potency and short duration of action. cis-42 was 13,036 times more potent than morphine and 29 times more potent than fentanyl; however, the corresponding diastereomer 43 was only 2778 and 6 times more potent, respectively. Compounds 40, 43, 47, and 57 are extremely short acting; all had dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The compounds obtained as diastereomers, were tested for analgesic activity on mouse hot plate test and the majority of the compounds displayed good activity. The most promising was compound ( 30 ) with an ED 50 value of 0.0025 mg/kg (Supplementary Information 7) [9194]. …”
Section: Insertion Of Methyl Substituent In Different Positions Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds obtained as diastereomers, were tested for analgesic activity on mouse hot plate test and the majority of the compounds displayed good activity. The most promising was compound ( 30 ) with an ED 50 value of 0.0025 mg/kg (Supplementary Information 7) [9194]. …”
Section: Insertion Of Methyl Substituent In Different Positions Of Thmentioning
confidence: 99%
“…3-methoxy-fentanyl analog has been prepared by traditional scheme (ketone-imine-amine-amide sequence) starting from 1-(2-phenylethyl)-piperidine-4-one ( 7 ), which was oxidized to give 3-hydroxy-piperidine-4-one dimethyl ketal, which was methylated to give 3-methoxy-piperidine-4-one ketal, converted to 3-methoxy-piperidine-4-one, which was further subjected to transformation to 3-methoxy-fentanyl. The effective dose (ED 50 = 0.00064 mg/kg) was obtained for the cis -isomer of synthesized compound [142]. …”
Section: Insertion Of Substituents Other Than Methyl Into the Differementioning
confidence: 99%
“…Finally, 22 precipitated withdrawal in morphine-tolerant mice, but to a lesser extent than did nalbuphine and naloxone. While this suggested that 22 may be a partial c~ agonist in the mouse, 22 was superior in the analgesic efficacy to the partial p agonist buprenorphine in the rat. 32 The overall pharmacological findings of this structurally unique fentanyl analog reveal a new central analgesic with an extraordinary high degree of therapeutic safety compared to the potent opioids presently employed in the clinic.…”
Section: B 4-(heteroaniiido)piperidinesmentioning
confidence: 76%
“…Recently, Ossipov ef al. reported a number of interesting findings in the ongoing examination of the pharmacology of Z3* Unlike fentanyl and alfentanil, the inhibition of gastrointestinal transit in mice produced by 22 was not completely dose-dependent; an asymptote was reached at 5 X MHP ED50. The intrathecal analgesia versus dose-response curve of 22 was similar to that of DPDPE, suggesting that it acts at least in part via delta opioid receptors.…”
Section: B 4-(heteroaniiido)piperidinesmentioning
confidence: 98%
“…To the best of our knowledge, the properties of trisubstituted aminopiperidines have been poorly investigated so far; only a few papers have dealt with this topic. [41][42][43][44][45][46][47][48][49] This prompted us to develop a new and convenient synthesis of trisubstituted aminopiperidine derivatives and to study their biological activity. We have succeeded in synthesizing new 4-aminopiperidine derivatives substituted in position 3 by groups bearing a carbamate (see Scheme 3) or a ureido (see Scheme 4) function.…”
Section: Introductionmentioning
confidence: 99%